Structural change and sectoral growth in selected East Asian countries - Haraguchi, Nobuya (UNIDO ViennaAT, 2010)
Compares selected East Asian economies, namely, Indonesia, Malaysia, Philippines, Republic of Korea and Thailand since 1975 and analyses their structural change relative to both the world's norm as well as comparators in the region.\n